Price Behaviour of Cassava in Kerala:An Econometric Analysis - Jayasree, K.; Resmi, P.; Satheesh Babu, K. (JOURNAL OF ROOT CROPS, 2013)
The study analyzed the price behaviour of cassava in Kerala during the period from January 1999 to June 2011. The growth in cassava prices was slow, but with high instability of 36.97%. Time series decomposition analysis was carried out to isolate the different components present in the price series. The single exponential smoothening model was found to capture the underlying trend in cassava prices with a low Mean Absolute Percentage Error (MAPE) value of 1.67. The seasonal decomposition analysis revealed that the months of March and April was typically characterized by a peak phase for cassava prices in Kerala. The period from September to November was also marked by a buoyant phase for cassava due to lean market arrival during this period. Even though no pronounced long term cycles were evident, three short cycles were identified during the study period. There were random effects in the price-but it oscillated more or less evenly around the mean value of 100, indicating that random factors were evenly occurring in cassava trading. As the shelf life of cassava tubers are too short, product development and diversification through processing and value addition is suggested to overcome the adverse seasonal and cyclical price movements.